Modern Concepts of Financial and Non-Financial Motivation of Service Industries Staff - GRYNKO, Tetiana; KRUPSKYI, Oleksandr; KOSHEVYI, Mykola; MAXIMCHUK, Olexandr (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
In modern conditions the questions of personnel management, including motivation, acquire new meaning. Particularly given the problems relevant to the service sector, where at the beginning of the XXI century employing more than 60% of the workforce in developed countries. These circumstances determine the need for a modern concept of material and immaterial motivation of service industries. Such factors determine the need for the development modern concept of material and immaterial motivation of service industries staff. To obtain indicated objective during research analyzed the existing concepts and paradigm of staff motivation with highlighting their advantages and disadvantages. The results obtained allowed to establish that scientific and expert community does not have the unified approach to the classification and identification of the most effective ones. Special attention is given to modern developments and approaches to the motivation problem. This fact caused the structure of follow studies, including three interlinked vectors: analysis of the essential content of the fundamental concepts in the field of staff motivation; defining features of employee motivation at the enterprises sphere of services; introduction to the key successful international practices which apply by service companies. In general, the results obtained enabled the author’s model of the modern concept of material and non-material motivation at the enterprises the service sector and the corresponding mechanism for the implementation.